CHALLENGES AND SOLUTIONS IN INTENSIVE LANGUAGE TEACHING - Safarova Dildora; Qo'chqorova Muxlisa; Keldiyorova Iroda (TADQIQOTLAR, 2025)
Annotation Intensive language teaching programs aim to accelerate language acquisition in a condensed timeframe, often requiring high learner motivation, consistent practice, and  effective  teaching  strategies.  However,  these  programs  come  with  unique challenges  such  as  learner  fatigue,  curriculum  overload,  and  limited  individual attention.  This  article  explores  common  problems  faced  in  intensive  language environments  and  proposes  practical  solutions,  such  as  differentiated  instruction, integration of technology, and psychological support. Understanding these challenges is  essential  for  improving  learning  outcomes  and  ensuring  student  well-being  in intensive settings.